Case Report: Epstein–Barr Virus Encephalitis Complicated With Brain Stem Hemorrhage in an Immune-Competent Adult - Huang, Lingtong; Zhang, Xuan; Fang, Xueling (Frontiers in Immunology, 2021)
Encephalitis caused by Epstein-Barr virus infection is uncommon, but most patients have a good outcome after symptomatic treatment. The infiltration of mononuclear cells in blood vessels and necrosis resulting from the immune response to Epstein-Barr virus infection in a very small number of patients seem to be the main cause of death. We describe a fatal case of Epstein-Barr virus encephalitis that was diagnosed by next-generation sequencing in an immune-competent adult but progressed to brainstem hemorrhage.